Ethnozoological importance of Eisenia fetida and experimental validation of its anticancer activity in ascites Dalton's lymphoma (DL) bearing mice - Manash Pratim Borah; Surya Bali Prasad (SpringerOpen, 2024)
Abstract Eisenia fetida, commonly known as the red earthworm, holds significant ethnozoological importance due to its traditional use in various cultures as a medicinal agent. This study aims to explore the potential anticancer effects of Eisenia fetida paste (EFP) and evaluate its therapeutic efficacy in mice with ascites Dalton's lymphoma (DL). The EFP extract demonstrated a significant antitumour effect, possibly by initiating programmed cell death and mitochondrial changes in the tumour cells. The viability of tumour cells exhibited a reduction over time due to EFP treatment. Comparative analysis with the reference drug cisplatin revealed that EFP exhibited fewer or no adverse effects on mutagenicity, hepatotoxicity, and nephrotoxicity in tumour-bearing hosts. EFP treatment was found to show progressive increase in the quantity of apoptotic DL cells over time suggesting a time-dependent impact on the induction of apoptosis in the treated groups. These results imply that EFP might serve as a safer substitute for cancer treatment and hold promise for developing new and improved therapeutic strategies against cancer. The main implication of the study is that EFP might serve as a safer substitute for cancer treatment. It suggests a promising avenue for developing new and improved therapeutic strategies against cancer, with the potential to enhance treatment outcomes while minimising adverse effects. Graphical abstract